The Theological Trends Among Modern Swahili Quranic Translations: الاتجاهات العَـقَـديـة في التراجم السواحلية المعاصرة للقـرآن الكريم - Alio Mohamed, Mohamed Sheikh (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2019)
ظهرت أول ترجمة سواحلية مطبوعة للقرآن الكريم في شرق إفريقيا سنة 3291م على يد قُ ّس إنجليزي يدعى غودفري ديل ( )Godfrey Daleكان تابعاً لإرسالية الجامعات إلى )، ثم تبعتها ترجمةUniversities’ Mission to Central Africa( وسط إفريقيا قاديانية على يد مبارك أحمدي عام 3291م. وفي عام 3292م ظهرت ترجمة أول ترجمة ُسنِّّيَّة كاملة على يد قاضي زنجبار ثم مفتي جمهورية كينيا ( )Chief Kadhiلاحقاً (3213-3291م) الشيخ عبد الله صالح الفارسي التي جاءت كر ٍّدّ َعقَدي على الترجمة القاديانية. ثم تتابعت الترجمات السواحلية للقرآن الكريم بعد ذلك حيث ظهرت ترجمات ُسنِّّيَّة، وشيعية، وإباضية أخرى. ومع وجود عدة دراسات حول هذه التراجم المذكورة غير الكلمات المفتاحية: شرق إفريقيا، القرآن، السَّواحلية، الترجمة، الاتجاهات العقدية. The first printed translation of The Holy Quran into Kiswahili in East Africa was authored by English Anglican Rev. Godfrey Dale, who was belong to Universities’ Mission to Central Africa (UMCA), England, and published in 1923. This was followed by a Qadiani translation by Mubarak Ahmadi in 1953. In 1969, the first Sunni complete translation was issued by the Kadhi of Zanzibar; the then Chief Kadhi of Kenya (1968-1981), Abdullah Saleh Al-Farsi, which came as response to the Qadiani translation. Afterward, several Sunni, Shia and Ibadi translations appeared. Despite these translations were studied in several studies, but none has classified them according to their theological affiliations. This research surveys the theological trends among modern Quranic Swahili translations in five folds that include Sunni, Shia, Ibadi, Qadiani and Christian missionary trends. The findings of the study attest that various theological approaches were applied in Swahili modern Quranic translations to convey different theological views. Key Words: East Africa, Quran, Kiswahili, Translation, Thelogical Trends.